Seleccion recurrente en el frijol comun para la mejora de caracteres multiples - Masaya S, P (Programa Cooperativo Regional de Frijol para Centroamérica, México y el Caribe (PROFRIJOL), 1989)
The disadvantages of different breeding methods are compared. Some methods such as pedigree hybridization are slow while others such as sequential selection require a large no. of populations for a specific character in each generation. Recurrent selection is recommended for improving bean lines since it facilitates the combination of several characters in just one var.; quantitative- type characters, such as yield or disease resistance, can also be improved. The original scheme proposed to implement these methods can be modified, depending on exptl. conditions and breeding needs. (CIAT)